An experimental study of nitrogen gas influence on the 443 ferritic stainless steel joints by double-shielded welding. Issue 9 (December 2016) - Zheng, Yong; Wang, Yichen; Li, Heng; Xing, Wenqing; Yu, Xinye; Dong, Peng; Wang, Wenxian; Fan, Guangwei; Lian, Jie; Ding, Min
Abstract This study addressed the comparison of microstructures and mechanical properties of gas tungsten arc welding (GTAW) of 443 super pure ferritic stainless steel which are protected by three different kinds of shielding gas during welding process: pure argon, argon in the inner layer combined with nitrogen in the outer layer (simple double-layer gas), and argon-5 %nitrogen in the inner layer combined with nitrogen in the outer layer (mixed double-layer gas). As a result, in the center of the welds protected by nitrogen and argon, it formed equiaxed grains which achieving the purpose of grain refinement, while there were all columnar grains in the weld protected by pure argon. The experimental results showed that the depth/width ratio of the welds shielded by simple double-layer gas had been increased. Additionally, with the addition of nitrogen in the shielding gas, the hardness and impact toughness of the weld metal and heat-affected zone (HAZ) were improved when the heat input was the same. The relationships between microstructures and mechanical properties of 443 ferritic stainless steel joints were studied by optical microscope and scanning electron microscope combined with energy-dispersive spectrometer.